If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(z + -2) = 7z + 1 Reorder the terms: 2(-2 + z) = 7z + 1 (-2 * 2 + z * 2) = 7z + 1 (-4 + 2z) = 7z + 1 Reorder the terms: -4 + 2z = 1 + 7z Solving -4 + 2z = 1 + 7z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-7z' to each side of the equation. -4 + 2z + -7z = 1 + 7z + -7z Combine like terms: 2z + -7z = -5z -4 + -5z = 1 + 7z + -7z Combine like terms: 7z + -7z = 0 -4 + -5z = 1 + 0 -4 + -5z = 1 Add '4' to each side of the equation. -4 + 4 + -5z = 1 + 4 Combine like terms: -4 + 4 = 0 0 + -5z = 1 + 4 -5z = 1 + 4 Combine like terms: 1 + 4 = 5 -5z = 5 Divide each side by '-5'. z = -1 Simplifying z = -1
| d/3-5=3 | | (-6)(12/9)= | | 18x-42x^2=0 | | 7.3x=-35.77 | | 28=-8u+4(u+2) | | 0.15(x+60)-0.02(x-40)=17.6 | | 6.5x+9x=8.5 | | 0.76+0.15y=0.841 | | 6x+21=3x-45 | | 0-3(m-2)=8 | | 9-5t=3t-15 | | 4r^6-9r^6=0 | | 8(x-1.2)=2.4 | | y(n)=0.25y(n-2)+x(n) | | 4x+4=4x+2 | | 8x-47=-x-17 | | 0.7x+11.8=x-2.09 | | 7x^2-56-41x=0 | | 5.8+0.9x=0.4 | | cos^3(x)+cos(x)=0 | | 6n+13=-14 | | 0.8n+2.9n-4.4=3 | | Cos(x)+1=2sin^2(x) | | 3d+1=22 | | 36/28 | | -2.8=-0.1p | | 20=8+3(12+x) | | 0.25d-11.6=2.45d | | 3q-3=3(q-1) | | 11.3-p=4.2 | | 6+5x+5x=76 | | 4x+20x=180 |